2011
DOI: 10.1155/2011/389542
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Focal Segmental Glomerulosclerosis in Pediatric Kidney Transplant Recipients: Effect of Rituximab

Abstract: Recurrence of focal segmental glomerulosclerosis (FSGS) after renal transplantation is a complication that often leads to graft loss. There is no consensus on the optimal treatment of recurrent FSGS. Rituximab, a monoclonal antibody to CD20, may be a useful treatment of this complication. Methods. We report four pediatric cases of recurrent FSGS treated with rituximab and plasmapheresis. Results. Four children (2M/2F), age 15.3 ± 2.6, with recurrent FSGS posttransplant were identified. Four doses of rituximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Despite successful results having been obtained [77][78][79][80][81][82][83][84][85][86] , other studies have shown a transient or even absent response to Rituximab ® [62,[87][88][89][90][91][92][93][94] (Table 1).…”
Section: Novel Therapeutic Optionsmentioning
confidence: 99%
“…Despite successful results having been obtained [77][78][79][80][81][82][83][84][85][86] , other studies have shown a transient or even absent response to Rituximab ® [62,[87][88][89][90][91][92][93][94] (Table 1).…”
Section: Novel Therapeutic Optionsmentioning
confidence: 99%
“…Since the year 2000, numerous case reports and small studies of the efficacy of rituximab in treating FSGS have been published [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The larger case series are summarized in Table 3.…”
Section: Treatmentmentioning
confidence: 99%
“…9,10 Furthermore, recent reports suggest that rituximab, a mAb to CD20 that depletes mature B cells, may be beneficial in some patients with the nephrotic syndrome. [11][12][13][14][15][16] However, the mechanisms by which rituximab alleviates the nephrotic syndrome are not yet known. Recent work has demonstrated that "natural antibody" contributes to tissue injury in a number of different diseases.…”
mentioning
confidence: 99%